Analysis of Tensile and Bending Properties of Epoxy Resin Matrix Composites Using Variations of Pandanus Tectorius Leaf Fibers - Bisono, Rahayu Mekar; Majedi, Farid; Arifin, Agus Choirul; Aziz R., M. Shafawallah Al. (International Journal of Science, Engineering, and Information Technology, 2023)
With the rapid development of science and technology, people need to be innovative and contemporary. New structures have been widely developed using composite materials made from natural fibers. This research aims to determine the effect of the volume fraction of epoxy matrix pandan tectorius leaf fibers with an epoxy matrix on tensile and bending strength to determine the best results of speciments. Pandan tectorius leaf fiber composites with epoxy resin matrix adopts hand-laying technology, and pandan leaf fiber composites are used for two tires. In this research, the volume ratio of pandan leaf fiber and epoxy resin matrix was found to be 40:60, 45:55, 50:50, 55:45 and 60:40. In the tensile test, the highest value in the average tensile strength of the epoxy-based pandan fiber material was 15.8 N/mm2, and the lowest value was observed when the fiber and matrix volume ratio (40:60) was changed. It occurs when the fiber and matrix volume ratio changes (50 : 50) is 12.2 N/mm2. Meanwhile, in the bending test, the highest average value of bending strength was for the variation of fiber and matrix volume fraction (60: 40), and for the lowest value for the variation of fiber and matrix volume fraction (40: 60), it was equal to 17.36 N/mm2.